Ecological and Social Evaluation of Coastal Tourism Destination Development: A Case Study of Balekambang, East Java - Hakim, Luchman; Retnaningdyah, Catur; Mukhzayadah, Mukhzayadah (Graduate School, Universitas Brawijaya, 2014)
Tourism is an important sector in developing countries to support economic growth, and coastal areas are famous destinations in tourism. The plan and design for Balekambang coastal area as a tourism destination in East Java, Indonesia has been formulated and published. However, it seems lack ecological and social perspectives. This study examines coral reefs structure as one of the ecological parameter and tourist perspectives as social parameter for destination development evaluation. Twenty belt-transects were established along Balekambang coastline, and then divided into three sections, the east, the centre and the west sections. Every belt-transect was 200m in length and consists of 15 plots 1 x 2m. The tourist perspectives to Balekambang were determined using questionnaire among 234 respondents. Based on the Morisita similarity index, the coral reef of east section consists of 2 zones, the centre consists of 5 zones and west section consists of 4 zones. The Shannon diversity index (H') among zones at every location was ranged. The diversity index of the east section ranged from 2.07 to 2.72, the central section ranged from 1.32 to 4.20, and the west section ranged from 3.13 to 4.20. Zones that were close to the coastline had lowest diversity indices than zones that located far from the coastline. Mostly, tourists stated that Balekambang was interesting, but the object of tourism should be added. Respondent knew there were forest surrounding Balekambang, and it has the possibility to develop as tourism destination. These findings argue that the forest conversion to cottage area that planned by the local government in the west section should be reviewed. It seems forest in the west section should be developed as a forest park to meet tourist needs and redistribute tourist concentration in the coastline. Keywords: Ecological and social evaluation, coastal, tourism, sustainable development, East Java.